Perceptions towards healthy diet of the Portuguese according to area of work or studies - Ferrão, Ana Cristina (2018)
The aim of this work was to evaluate the perceptions towards a healthy diet among the participants who had a work or studies in areas related to diet and nutrition and those who did not. For this purpose, anonymous questionnaire data were collected in a cross-sectional study on a non-probabilistic sample of 902 participants living in Portugal. The results showed that the participants’ perceptions were, in general, compliant with a healthy diet (scores between 0.5 and 1.5, on a scale from -2 to +2). However, were found significant differences between gender (p = 0.004), with a higher average score for women, between the different civil state groups (p = 0.016), with a higher score for the single participants, between the participants who were responsible for buying their own food and those who were not, with a higher mean value for those who were not and also regarding the living environment, being the highest score for the participants who lived in rural areas. The variable area of work or studies also showed significant differences (p = 0.001), so that people who had a work or studies related to agriculture obtained a higher score. Regarding this variable, the mean values of nutrition and food areas were not statistically different between them, but were statistically different from the mean values of psychology and health areas. The participants who had a work or studies in areas where are addressed diet and nutrition related issues achieved a higher mean score (0.72 ± 0.35) when compared to the participants who did not have (0.58 ± 0.30). However, despite the results, it is important to continue developing campaigns that better communicate nutritional aspects, so that people can increase their knowledge on this subject. Acknowledgments: This work was prepared in the ambit of the multinational project EATMOT from CI&DETS Research Centre (IPV - Viseu, Portugal) with reference PROJ/CI&DETS/CGD/0012.